PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA KURIKULUM MERDEKA BELAJAR - Pinta Romaito Br Sagala; Lily Rohanita Hasibuan (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to determine: 1) the effect of the snowball throwing learning model on the learning motivation of class X students at SMA Negeri 1 Merbau, 2) the effect of the snowball throwing learning model on the learning outcomes of class X students at SMA Negeri 1 Merbau, 3) the effect of the snowball learning model throwing on the motivation and learning outcomes of class X students at SMA Negeri 1 Merbau. This study used a quantitative approach with a quasi-experimental design. The design model uses a pretest posttest control group design The sampling technique was carried out using a random sampling technique, namely class X-2 totaling 28 students as the control class which was given the conventional learning model treatment ,and class X-1 totaling 28 students as the experimental class being treated with the Snowball Throwing learning model. Based on the results of the study, the univariate Manova-Test obtained the F value for learning motivation, namely 8.751; p < 0.05 and the F value for learning outcomes is 5.219; p < 0.05 while in a multivariate manner motivation and learning outcomes obtained the F value for namely 5.204; p < 0.05. Univariate and multivariate test results have a significance of <0.05. That is, the values of F are all significant. So it can be concluded that there is an influence of the Snowball Throwing learning model on student motivation and learning outcomes in the independent learning curriculum. Keywords: Learning Outcomes; Learning Motivation; Snowball Throwing Learning Model